(3GdeMGSHI GdeJhSWI(B(1) :s (3eTGcd bjGS GdONd hGdeMGSHI hGdEaUGM Yf GdCUhd bUjQI GdCLd (B/s - (3fhQ, CMeO eMeOs; (3CHh GdecGQe, hUaj YHO GdaJGM s; (3GdSjO TMGJI, TMGJI s ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2003)
(3GdEWGQ GdacQj ddeMGSHI GdeGdjI(B-(3JMbb GdEjQGOGJ hGdeUQhaGJ hbjGS UGaj Ch NSGQI GdaJQI habG deYGjjQ GdeMGSHI GdeUQjI hGdOhdjI(B-(3aj GdejRGfjI GdYehejI hLQO hJbjje GdCUhd GdeJOGhdI habG deYGjjQGdeMGSHI GdeUQjI hGdOhdjI aj HYV GdeTGcd GdeQJHWI HGdeNRhf(B"(3eTGcd HVGYI GdCeGfI(B"s
Keywords: (3GdONds; (3GdeMGSHIs; (3GdejRGfjIs